2017
DOI: 10.1038/hr.2017.76
|View full text |Cite
|
Sign up to set email alerts
|

A study on clinicoradiological characteristics and pregnancy outcomes of reversible posterior leukoencephalopathy syndrome in preeclampsia or eclampsia

Abstract: Reversible posterior leukoencephalopathy syndrome (RPLS) is a critical maternal complication in preeclampsia or eclampsia during pregnancy. However, studies regarding the clinicoradiological and outcome differences between RPLS and non-RPLS pregnancies are scarce. We aimed to explore the incidence of RPLS, and summarize the clinicoradiological characteristics and pregnancy outcomes. We consecutively collected a total of 100 patients who were diagnosed with preeclampsia or eclampsia, and examined via magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…The average SLEDAI score could reach 26.3, and hormones were needed to increase to control the symptoms after the onset of PRES, which also support the above statement that the high activity of SLE is related to mortality, mainly because the high activity of SLE can lead to multiple organ diseases and increase the mortality rate. Previous literature reported that the incidence of PRES in pregnant patients can reach 0.22% [ 6 ]; this article found that pregnancy was the first cause of PRES, which is consistent with it. The proportion of pregnant patients in the death group was significantly less than that in the survival group; moreover, we confirmed that pregnancy was a protective factor for the death of PRES in multivariate analysis, showing that PRES in pregnant patients has the characteristics of high morbidity and low mortality, which is consistent with previous studies [ 5 , 6 , 8 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The average SLEDAI score could reach 26.3, and hormones were needed to increase to control the symptoms after the onset of PRES, which also support the above statement that the high activity of SLE is related to mortality, mainly because the high activity of SLE can lead to multiple organ diseases and increase the mortality rate. Previous literature reported that the incidence of PRES in pregnant patients can reach 0.22% [ 6 ]; this article found that pregnancy was the first cause of PRES, which is consistent with it. The proportion of pregnant patients in the death group was significantly less than that in the survival group; moreover, we confirmed that pregnancy was a protective factor for the death of PRES in multivariate analysis, showing that PRES in pregnant patients has the characteristics of high morbidity and low mortality, which is consistent with previous studies [ 5 , 6 , 8 ].…”
Section: Discussionsupporting
confidence: 84%
“…Similar to previous studies, most of the patients were young women [1][2][3][4][5][6][7][8], which is related to the specific disease states that PRES occurs in. This article found that pregnancy and SLE accounted for the first and second causes of PRES, respectively, 47.8% and 38.0%, which explains the age and gender characteristics of PRES.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The risk factors of PE and eclampsia are to some extent the risk factors of PRLS, arising from physiological changes during pregnancy. 7 The results of this study found that, in the control group, the changes in systolic blood pressure and mean arterial pressure were more obvious ( P< 0.05). It suggested that, elevated blood pressure was an important factor in the formation of PRLS.…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, Thl7 and Treg cells may be involved in embryo immune rejection and inflammation of pathological pregnancy such as PE. 2 …”
Section: Introductionmentioning
confidence: 99%